2015
DOI: 10.1111/joor.12303
|View full text |Cite
|
Sign up to set email alerts
|

Dental, skeletal asymmetries and functional characteristics in Class II subdivision malocclusions

Abstract: Treatment outcomes of Angle Class II subdivision malocclusions may be compromised because of the uncertainty of the aetiology. Previous studies have reported controversial ideas about the origins, but the existence of a primary contributor still remains unknown. Functional factors have been mentioned as a probable cause, but until now, there have been no supporting data. This study was a cross-sectional investigation of the characteristics of Angle Class II subdivision malocclusion, including dental, skeletal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…9,10,11 The current study corroborated the recent findings of Li et al, 11 who reported right-and left-side differences in spatial positioning of glenoid fossae of patients with Class II subdivision malocclusion. Although they assessed the position of glenoid fossae in Class II subdivision in comparison with Class I patients, the present study is the first to have compared Class II subdivision with skeletal Class II patients.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…9,10,11 The current study corroborated the recent findings of Li et al, 11 who reported right-and left-side differences in spatial positioning of glenoid fossae of patients with Class II subdivision malocclusion. Although they assessed the position of glenoid fossae in Class II subdivision in comparison with Class I patients, the present study is the first to have compared Class II subdivision with skeletal Class II patients.…”
Section: Discussionsupporting
confidence: 82%
“…Based on the standard deviation of 2.149 mm reported by Li et al 11 for the primary outcome of the current research (ie, sagittal position of the glenoid fossa), an alpha significance level of 0.05 and a power of 0.80 to detect differences between groups greater than 1.3 mm, a sample size of 41 patients per group was adopted. The sample consisted of 82 orthodontic patients (49 male and 33 female), all aged 12 to 17 years.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Agenesis has also been correlated with Class II malocclusions (15); despite hypodontia being one of the most common anomalies in our sample, it was not associated with any malocclusion. The cause of Class II subdivision malocclusion is multifactorial, comprising skeletal, dental and functional features (41). In that way, anomalies could contribute to develop these malocclusions.…”
Section: Discussionmentioning
confidence: 99%